Fitness, fatness and fibre type : predicting insulin resistance in Māori : a thesis presented in partial fulfillment of the requirements for the degree of Doctor of Philosophy, Massey University, Palmerston North, New Zealand - Warbrick, Isaac; Warbrick, Isaac (Massey University, 2010)
No abstract
Keywords: Maori health; Diabetes; Physical fitness